Golf director competencies, human resource management practices and customer retention within the Malaysian golf clubs / Samira Partanian - Samira , Partanian (2020)
Golf is a popular sport worldwide. Many studies have described management competencies in several sport contexts and have revealed that human resource is the most common denominator for successful sports club practice. However, little work has been done to identify and explain contemporary Human Resource Management (HRM) practices of staff, including directors of golf clubs related to member retention. The purpose of this study was to examine the current level and the participants' quality perceptions in the relationship among competencies of directors, HRM practices of staff, and member retention within the Malaysian Golf Clubs to advance the causal relationships among them. It was also aimed to develop a conceptual framework and a measurement model. A survey was conducted in the Malaysian Golf Clubs using the Competencies of Golf Course Directors, Employee’s HRM Practices and Member Retention Behavior questionnaires. A total of 200 questionnaires were distributed among both staff and members who were selected randomly from 34 golf clubs. Based on the data collected and theory of Total Quality Management, a research model was developed consisting of director competencies (golf operation and client care development), member retention behavior, and HRM practices of staff. Client Care Development had a positive and significant effect (β= 0.49, p < 0.05). Golf operation competencies showed a positive effect on customer’s retention behavior (β= 0.37, P < 0.05). R2 of the current model for member retention was 0.65, which accounts for 65.4% of the reachable fitness. Higher level of both director’s competencies (Golf operation and Client Care Development) resulted in a better retention behavior of customers and a better HRM practices of staff (R2 = 0.59). The HRM mediation increased the effect of director’s competencies on the member retention. The R2 for member retention behaviors was 0.68, implying that 68% of member retention behaviors can be explained by client care development, golf operation and HRM practices. The effects of both client care development (β=0.35, p<0.05) and Golf operation competencies (β=0.474, P<0.05) on HRM practices of staff were positive and significant. This means that higher level of both director’s competencies (Client Care Development and Golf operation) will tend to achieve a better HRM practices of staff. The boot strapping results showed positive and significant effects of golf operation, (β= 0. 0.32, p < 0.05) and client care development (β= 0. 31, p < 0.05) on member retention behaviors. This indicates that the direct effects of golf operation and client care development on member retention behaviors were significant after mediation of HRM practices. The structural equation modeling was done to test the model. The model showed a desirable goodness of fit, meaning that impact of directors’ competencies, staff HRM services and customer return to the Malaysian Golf Clubs was positive and meaningful. In conclusion, directors of Golf Club in Malaysia should evolve continually to manage changes and hold several skills in Golf, technical aspects, HR, and business operations. The findings of this thesis provide golf course directors in Malaysia with important information for adequate preparation in golf management.